2020
DOI: 10.1097/spv.0000000000000872
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Energy-Based Devices

Abstract: This clinical consensus statement on vaginal energy-based devices (EBDs) reflects statements drafted by content experts from the American Urogynecologic Society’s EBD writing group. The American Urogynecologic Society's EBD writing group used a modified Delphi process to assess statements that were evaluated for consensus after a structured literature search. A total of 40 statements were assessed and divided into 5 categories: (1) patient criteria, (2) health care provider criteria, (3) efficacy, (4) safety, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 57 publications
0
35
0
Order By: Relevance
“…The recent consensus paper published by Alsheiek et al [27] concluded that a short‐term benefit could be achieved after a fractional laser, but most studies lack long‐term follow‐up and control groups. Our study differs from previous reports given its longer follow‐up period of 12 months, and by the addition of well‐accepted validated outcome measures, including subjective, objective, and histological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The recent consensus paper published by Alsheiek et al [27] concluded that a short‐term benefit could be achieved after a fractional laser, but most studies lack long‐term follow‐up and control groups. Our study differs from previous reports given its longer follow‐up period of 12 months, and by the addition of well‐accepted validated outcome measures, including subjective, objective, and histological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the complication rates were low and the most commonly reported side effect was temporary noninfectious vaginal discharge. Although larger studies are needed, this initial report should alleviate concerns for major complications such as vaginal burns or scarring described with ablative vaginal laser therapy [23,24].…”
Section: Discussionmentioning
confidence: 97%
“…The SoLá Pelvic Therapy Laser is a nonablative class IV NIR laser capable of transmitting both 810 and 980 nm wavelengths to pelvic structures [21]. The nonionizing and nonthermal effect emitted by the device avoids the serious side effects such as vaginal scarring and burns reported [22] when traditional lasers (CO 2 and Er: Yag lasers) are used to treat vaginal conditions such as atrophy, laxity and incontinence [23,24].…”
mentioning
confidence: 99%
“…The International Urogynecological Association (IUGA) issued a consensus statement echoing concerns about the devices, and an International Continence Society/International Society for the Study of Vulvovaginal Disease Best Practice Consensus Statement did not recommend the laser for "routine treatment of vaginal atrophy or urinary incontinence unless treatment is part of a well-designed trial or with special arrangements for clinical governance, consent, and audit." 2 In May 2020, as evidence remains limited (although 522 studies are ongoing in coordination with the FDA), the American Urogynecologic Society (AUGS) published a clinical consensus statement from a panel of experts in female pelvic medicine and reconstructive surgery. The panel had about 90% consensus that there is short-term efficacy for the laser with GSM and dyspareunia.…”
Section: What This Evidence Means For Practicementioning
confidence: 99%
“…But we only have outcomes data that lasts a maximum of 1 year. 2 A problem with our VeLVET trial, 3 which was published in Menopause, and the Cruz and colleagues' trial from South America, 4 both of which compared the CO2 laser to estrogen and had randomized groups, was that they were limited by the outcome measures used, none of which were consistently validated. But these studies also had small numbers of participants and short-term follow-up.…”
Section: What This Evidence Means For Practicementioning
confidence: 99%